Systematic review with meta‐analysis: post‐operative complications and mortality risk in liver transplant candidates with obesity. Issue 3 (10th May 2017) - Barone, M.; Viggiani, M. T.; Losurdo, G.; Principi, M.; Leandro, G.; Di Leo, A.
Summary: Background: International guidelines rate class III (morbid) obesity (body mass index [BMI]≥40 kg/m 2 ) as a relative contraindication for liver transplantation (LT) requiring further research. Moreover, data on the mortality risk in candidates with a BMI: 30‐34.9 and 35‐39.9 kg/m 2 (class I and class II obesity, respectively) are weak. Aim: To compare post‐operative complications and mortality risks in all obese candidates vs candidates with a BMI: 18.5‐29.9 (normal/overweight) assumed as controls. Methods: We searched the Cochrane library, PubMed, Scopus, Web‐of‐Science and article reference lists, restricted to the English language, and selected cohort studies analysing the following outcomes: all‐causes mortality (at 30 days, 1‐2‐3‐5 years), post‐operative and cardiopulmonary complications, hospital and intensive care unit (ICU) length of stay. Two reviewers independently extracted the studies data and a third one resolved discrepancies. Results: Twenty‐four studies comprising 132 162 patients met the inclusion criteria. As compared to controls, mortality risk was increased at all time‐periods (except at 3 years) for a BMI≥40, at 30 days for a BMI: 30‐34.9 and in none of the considered time‐periods for a BMI: 35‐39.9. Post‐operative complications were significantly higher for a BMI>30 and 30‐34.9. Due to the shortage/absence of data, we evaluated cardiopulmonary complications, hospital and ICU length of stay only in the BMI≥30 category. In these patients, only cardiopulmonary complications were increased as compared to controls. Conclusions: Morbid obesity has an impact on patients' survival after LT. However, since even a BMI>30 increases post‐transplant complications, new strategies should be included in the LT programme to favour weight loss in all obese candidates. Abstract : Linked Content This article is linked to Townsend and Newsome et al and Barone, Barone et al and Liu et al papers. To view these articles visithttps://doi.org/10.1111/apt.14179, https://doi.org/10.1111/apt.14195, https://doi.org/10.1111/apt.14446 andhttps://doi.org/10.1111/apt.14425 .